2021
DOI: 10.1021/acsbiomaterials.1c00805
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Patterning of Tissue Spheroids Using Polymer Microcapsules Containing Iron Oxide Nanoparticles

Abstract: Magnetic tissue engineering is one of the rapidly emerging and promising directions of tissue engineering and biofabrication where the magnetic field is employed as temporal removal support or scaffold. Iron oxide nanoparticles are used to label living cells and provide the desired magnetic properties. Recently, polymer microcapsules loaded with iron oxide nanoparticles have been proposed as a novel approach to designing magnetic materials with high local concentrations. These microcapsules can be readily inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…For nanoparticle-loaded homogenous spheroids, it has previously been shown that spheroids fuse rapidly and agglomerate in a pattern depending on the magnetic field, also referred to as micropatterning. [20,88] Hence, spheroids can be guided by magnetic forces and used as controllable building blocks in tissue engineering. [89] Magnetic janus-loading not only enables positioning of whole spheroids depending on the magnetic field, but also which side of the spheroid is in the direction of the magnet.…”
Section: Micropatterning Of Spheroidsmentioning
confidence: 99%
“…For nanoparticle-loaded homogenous spheroids, it has previously been shown that spheroids fuse rapidly and agglomerate in a pattern depending on the magnetic field, also referred to as micropatterning. [20,88] Hence, spheroids can be guided by magnetic forces and used as controllable building blocks in tissue engineering. [89] Magnetic janus-loading not only enables positioning of whole spheroids depending on the magnetic field, but also which side of the spheroid is in the direction of the magnet.…”
Section: Micropatterning Of Spheroidsmentioning
confidence: 99%
“…Nowadays, a method of assembling cells by gravity using a cell culture plate capable of blocking cell adhesion on the well is promising. , While modifying the manuscript, a research paper on the arrangement of spheres using magnetic nanoparticles was published. This author has also succeeded in arranging cells in an arbitrary morphology using a magnetic field . As for the other methods, the application of a microchannel has been reported .…”
Section: Results and Discussionmentioning
confidence: 97%
“…Importantly, the high payload capability offered by microcapsules enables applications where stronger dragging forces are needed, such as in spatial control of cells [108,109]. For instance, IONP-loaded polymeric microcapsules have been recently used to magnetize cells assembled into spheroids, which could be then used for magnetic patterning and biofabrication of tissue-engineering constructs [110]. Magnetic microcapsules are therefore valuable tools for magnetic tissue engineering, in which magnetic forces serve as temporary supports to assemble biological structures from individual cells or spheroids.…”
Section: Magnetic Microcapsulesmentioning
confidence: 99%
“…Cells, cells spheroids, or matrices containing cells can be modified with magnetic particles and then, under the application of a magnetic field, can be induced to assemble into morphologies that mimic the structure of target organs (e.g., rings for vessels, sheets for skin, etc.) [110,424]. Thus, magnetic tissue engineering emerges as an important tool to enhance bioprinting functionality and realize future multiplex bioconstructs and organ replicas.…”
Section: Perspectivesmentioning
confidence: 99%